Antithrombotic medication in cancer-associated thrombocytopenia: Current evidence and knowledge gaps. (December 2018) - Leader, A.; ten Cate, H.; Spectre, G.; Beckers, E.A.M.; Falanga, A.
Graphical abstract: Highlights: Thrombocytopenia is an adverse prognostic marker in arterial and venous thrombosis. Changes in anticoagulation (AC) if platelets < 50 × 10 9 /L; lower for antiplatelets. AC for acute venous thrombosis, with increased transfusion target or dose reduction. Consider holding AC in lower risk atrial fibrillation. Use aspirin in acute coronary syndrome, especially when platelets > 30 × 10 9 /L. Abstract: In cancer patients, antithrombotic medications (i.e. anticoagulation or antiplatelet therapy) are frequently prescribed for prior or new indications such as venous thromboembolism or stoke prevention in atrial fibrillation. Balancing the risks of bleeding and thrombosis during periods of thrombocytopenia represents a significant challenge. Management is informed mainly by expert opinion and several recent retrospective studies on venous thromboembolism. The main management options include no change, temporarily withholding antithrombotic therapy, reducing dose, changing the regimen, and increasing the platelet transfusion threshold. Important recent advances in knowledge include the prognostic importance and apparent safety of aspirin in acute myocardial infarction and thrombocytopenia and data suggesting a low risk of recurrent venous thromboembolism in autologous stem cell transplantation patients who had anticoagulation withheld. This paper will review the literature on antithrombotic medication in thrombocytopenic patients with cancer. The significant knowledge gaps will be summarized and considerations for practice and research will be provided.